Interfaith Families: How to Communicate Effectively for Education and Family Happiness - Hidayatullah, Fauzan; Puspitasari, Savira Widya; Rahman, Rosnani Abdul; Mulawarman, Mulawarman (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This study aims to describe effective communication patterns in interfaith families and their implications for education and household well-being. The background of the research is based on the phenomenon of interfaith couples who face challenges in building harmony, particularly in decision-making, child education, and the instillation of family values. The research method used is a qualitative approach with a case study technique on several interfaith couples in Makassar City. Data were collected through in-depth interviews, observation, and documentation, then analyzed thematically. The results show that effective communication characterized by openness, empathy, equality, and conflict management becomes an essential factor in creating harmony in interfaith families. Moreover, healthy communication plays a role in shaping inclusive family education, instilling values of tolerance, and supporting the growth of happiness within the household. The conclusion emphasizes that appropriate communication patterns can serve as a bridge to strengthen family education and maintain the emotional stability of interfaith couples.